SWOT ANALYSIS OF HYDROGEN ECONOMY - Oravec Dominik; Martins Florinda F.; Janicek Frantisek; Farkas Smitkova Miroslava (Journal of Energy Technology, 2025)
The paper deals with the types of hydrogen production, methods for its storage and transport, and possibilities of the end use of hydrogen. The basics of the hydrogen economy are described briefly, and then the SWOT analysis is performed of the hydrogen economy. The strengths, weaknesses, opportunities, and threats of the hydrogen economy are summarized in the SWOT analysis. The biggest problems and threats, with the possibilities of solving those problems, are summarized based on that analysis. The SWOT analysis considers aspects of the hydrogen economy e.g. energy demands, financial difficulty, safety, and awareness about hydrogen. The Conclusions involve suggestions on how to avoid the above-mentioned awareness, and how to increase hydrogen utilization.